2018
DOI: 10.1111/cdoe.12367
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in assessing the association between periodontitis and caries among adolescents

Abstract: We found an association between caries and periodontitis among adolescents. The "severity" of periodontitis was negatively associated with enamel/dentin caries, whereas the "extent" of periodontitis was positively associated with dentin caries irrespective of the analytical approach employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
5
20
1
Order By: Relevance
“…Findings concerning the relationship between periodontitis and dental caries are contradictory. Prior research on this association has been heterogeneous, some has documented a positive association [56], however, recent research showed a negative correlation between the severity of periodontitis and caries prevalence [57], which is consistent with our findings. A possible explanation for the lower decay score among the periodontitis group (see Table 2), could be our finding of a lower consumption rate of sweets in the periodontitis group (see Table 3) that had been demonstrated in the study.…”
Section: Discussionsupporting
confidence: 91%
“…Findings concerning the relationship between periodontitis and dental caries are contradictory. Prior research on this association has been heterogeneous, some has documented a positive association [56], however, recent research showed a negative correlation between the severity of periodontitis and caries prevalence [57], which is consistent with our findings. A possible explanation for the lower decay score among the periodontitis group (see Table 2), could be our finding of a lower consumption rate of sweets in the periodontitis group (see Table 3) that had been demonstrated in the study.…”
Section: Discussionsupporting
confidence: 91%
“…These constructs were determined according to the loading of related clinical features, indicating that the different dimensions of the disease were properly grouped. While the latent periodontal variables were differently associated to dental caries, the use of an observed categorical periodontal variable failed to detect an association . These findings, thus, suggest that a broader approach should be considered when investigating the relationship between conditions with multiple dimensions, such as MetS and periodontitis.…”
Section: Introductionmentioning
confidence: 89%
“…Model fit was estimated using CFI, TLI, RMSEA, and CMIN / DF. Values of CFI and TLI close to .95 or higher are an indication of good fit (Nascimento, Baelum, Dahlen, & Lopez, 2018), a CMIN / DF ratio lower than 3 is considered a good fit (Eckhaus & Davidovitch, 2019;Wu, Chen, & Yuan, 2018). RMSEA values should be ≤ .06 (Hu & Bentler, 1999).…”
Section: Survey Analysismentioning
confidence: 99%